2021
DOI: 10.1038/s41598-021-93189-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel interaction of FUS and syntaphilin may explain synaptic and mitochondrial abnormalities caused by ALS mutations

Abstract: Aberrantly expressed fused in sarcoma (FUS) is a hallmark of FUS-related amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Wildtype FUS localises to synapses and interacts with mitochondrial proteins while mutations have been shown to cause to pathological changes affecting mitochondria, synapses and the neuromuscular junction (NMJ). This indicates a crucial physiological role for FUS in regulating synaptic and mitochondrial function that is currently poorly understood. In this paper we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Characterization of early synaptic changes in pre-symptomatic FUSWT mice showed mitochondrial abnormalities in the pre-synaptic motor nerve terminals lead to smaller NMJs, loss of synaptic vesicles and synaptophysin (Syp) expression in the absence of motor neuron loss (So et al, 2018). Changes in mitochondrial abundance have also been observed in ALS/FTD-FUS patients and other disease models (Tradewell et al, 2012;Deng et al, 2015;Tsai et al, 2020), which may occur due to aberrant interactions with mRNA or protein interactions that lead to global changes in protein synthesis (Nakaya and Maragkakis, 2018;Tsai et al, 2020;Salam et al, 2021). Future studies will need to focus on understand the mechanisms by which FUSWT and FUS variants affect mitochondrial function in ALS/FTD-FUS disease models.…”
Section: Fus: Synaptic Dysfunction In Als/ftd Models Of Diseasementioning
confidence: 99%
“…Characterization of early synaptic changes in pre-symptomatic FUSWT mice showed mitochondrial abnormalities in the pre-synaptic motor nerve terminals lead to smaller NMJs, loss of synaptic vesicles and synaptophysin (Syp) expression in the absence of motor neuron loss (So et al, 2018). Changes in mitochondrial abundance have also been observed in ALS/FTD-FUS patients and other disease models (Tradewell et al, 2012;Deng et al, 2015;Tsai et al, 2020), which may occur due to aberrant interactions with mRNA or protein interactions that lead to global changes in protein synthesis (Nakaya and Maragkakis, 2018;Tsai et al, 2020;Salam et al, 2021). Future studies will need to focus on understand the mechanisms by which FUSWT and FUS variants affect mitochondrial function in ALS/FTD-FUS disease models.…”
Section: Fus: Synaptic Dysfunction In Als/ftd Models Of Diseasementioning
confidence: 99%
“…Despite reduced expression of FMRP at synapses, our puromycin translation assay did not support the hypothesis of increased protein translation capabilities in the FUS-ALS lines at synapses. Furthermore, Salam et al., (2021) observed that overexpression of mutant FUS R514G alters synaptic number in primary neurons, accompanied by increased global protein translation ( Salam et al., 2021 ). Our data show that R514G does not enhance global puromycin translation and differs from R521C iPSC-derived neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant FUS may also be involved in the ERmitochondria communication defects as it is identified to activate GSK-3β responsible for the VAPB-PTPIP51 defective interaction (Stoica et al, 2016). ALS-associated axonal cargo transport defects may involve FUS protein as it is recently recognized to interact with Syntaphilin (involved in mitochondrial tethering) and a mutated form of FUS alters this interaction causing mitochondrial abnormalities observed in ALS (Salam et al, 2021).…”
Section: Altered Function Of Fus Protein Causes Als-linked Mitochondr...mentioning
confidence: 99%